Improving Students' Mathematics Learning Achievement on the subject of Integers through the Think-Pair-Share Cooperative Learning Model in Class V SD Negeri 3 Maligano - kamarudin kamarudin (Amanah: Jurnal Amanah Pendidikan dan Pengajaran, 2021)
This study aims to improve the mathematics learning achievement of fifth-grade students of SD Negeri 3 Maligano through the Think-Pair-Share (TPS) type of cooperative learning model. This type of research is classroom action research (CAR). The procedures of this research are (1) planning, (2) implementing actions, (3) observing and evaluating, (4) reflection. The sources of data in this study are teachers and students. The types of data obtained are qualitative and quantitative data consisting of observation sheets, learning outcomes tests and journals. The instruments used in this research are learning outcomes evaluation tests for three cycles and observation sheets for teachers and students during the teaching and learning process. Students who received research actions in this study were fifth-grade students of SD Negeri 3 Maligano semester II for the 2020/2021 academic year, with a total of 32 students consisting of 17 boys and 15 girls. After the test, the students' learning mastery classically was obtained. The initial examination reached 6%, the first cycle test reached 9%, the second cycle test reached 64%, and the third cycle test reached 94%. From the implementation of the three cycles in learning, it can be concluded that the Think-Pair-Share type of cooperative learning model can improve the mathematics learning achievement of fifth-grade students of SD Negeri 3 Maligano.